Surgical planning with patient-specific three-dimensional printed pancreaticobiliary disease models – Cross-sectional study. (August 2020) - Bati, Ayse Hilal; Guler, Ezgi; Ozer, Mehmet Asim; Govsa, Figen; Erozkan, Kamil; Vatansever, Safa; Ersin, Muhtar Sinan; Elmas, Zehra Nevra; Harman, Mustafa
Abstract: Background: Three-dimensional (3D) printing has been increasingly used in medical applications with the creation of accurate patient-specific 3D printed models in medical imaging data. This study has been planned based on the fact that research on 3D printing in pancreaticobiliary disease is limited due to lack of studies on validation of model accuracy. Methods: This is an innovative study where general surgery residents are presented 5 distinct hepatopancreatobiliary disease scenarios to generate a perception and required to compare their perception level of these cases with magnetic resonance cholangiopancreatography (MRCP), 3D images and 1:1 solid models that the pathology, diverse diagnosis and presurgery diagnosis stages can be observed. This study is single-centered. Results: The dilated pancreaticobiliary intervention based on scenarios for general surgery residency was more original since there was no prior study that includes both model building and the evaluation of the perception created by the model. Five scenarios provided qualitative assessment with results showing the usefulness of 3D models when used as clinical tools in preoperative planning, simulation of interventional procedures, surgical education, and training. The perception level in the 3D model, MRCP (Z: 3.854, p: 0.000) and the 3D image (Z: 2.865, p: 0.004) was higher; likewise, the 3D-STL image was higher compared to the MRCP image (Z: 3.779, p: 0.000). All subspecialists agree that 3D models provided better understanding of dilated pancreaticobiliary pathoanatomy and improved surgical planning. Conclusions: A thoroughly outlined genuine patient situation layout aimed for general surgery training can be installed and monitored with the support of 3D printing technology of this study. This can be utilized to develop the comprehension of pathoanatomical variations of complex pancreaticobiliary illness and to adopt a surgical approach. Highlights: To evaluate a well-structured real patient scenario setup for pancreticobiliary surgery training. A five-station carousel is formed for the study. CT, 3D-STL images and 1:1 solid models of the cases are included in each station. All subspecialties agree 3D models provided better understanding pathoanatomy and improved preplanning.